The Impact of Active Case Finding among Household Contacts of Sputum Smear Positive Patients on the Case Detection Rate. - Elbashir, Ibtisam M E; Dafalla, Nusaiba A; Hussain, Salwa E; Hamza, Hassan (Gezira Journal of Health Sciences, 2012)
Background: Tuberculosis is one of the major public health problems which is targeted by global control. One of the main strategies for control of tuberculosis is to achieve a case detection rate of 70% or more of sputum smear positive cases of the estimated annual new infections. Objectives: This study was conducted to assess the impact of active case finding among sputum smear positive household contacts in great Wad Madani locality Gezira State, Central Sudan. Methods: The study was a prospective longitudinal study in which all household contacts of sputum smear positive cases who were diagnosed during the study period and who accept to participate in the study were home visited and  screened  using adapted World Health Organization (WHO) screening forms for the main symptoms and signs of tuberculosis. Those who were found to be symptomatic were further investigated by sputum examination (three specimens), for adults. chest X ray and Mantoux test for unvaccinated under five children. Results and conclusions: A total of 161 cases were detected passively during the study period, 153 agreed to participate in the study. A total of 659 household contacts were screened. Of those 24 were found to be sputum smear positive giving a prevalence of 3.6% among household contacts and the case detection rate increased from 35.4/ 100.000 through passive case finding, to 40.8/100.000 through active case finding giving that active case finding can increase the case detection rate which is one of the main goals of tuberculosis control strategies.    ملخص: خلفية :السل احد مشاكل صحة المجتمع الهامة و مستهدف بتحكم عالمي . أحدى الاستراتيجيات الهامة للتحكم في السل هو إنجاز معدل رصد الحالة 70% أو اكثر من مسحة القشع الإيجابية لحالات العدوى (الأخماج) الجديدة المتوقعة سنوياً. الأهداف : أجريت الدراسة لتقييم أثر رصد الحالات النشطة وسط المخالطين المنزليين (الأسريين) بقشع إيجابي المسحة في محلية ود مدني الكبرى – السودان. الطرق : هذه دراسة توقعية طولانية شملت كل المخالطين المنزليين لحالات القشع موجب المسحة الذين تم تشخيصهم خلال فترة الدراسة و قبلوا بالمشاركة في البحث أجريت لهم زيارات منزلية و أجري المسح باستخدام فورمات منظمة الصحة العالمية لمسح الاعراض و العلامات لمرض السل. النتائج والخلاصه : تم رصد 161 حالة سلبياً خلال فترة الدراسة منهم 153 قبلوا بالمشاركة في الدراسة، تم مسح 659 من المخالطين المنزليين. القشع موجب المسحة وجد في 24 حالة مما أعطى معدل شيوع 3.6% وسط المخالطين المنزليين و ارتفاع معدل رصد الحالة من35.4/100.000  فى الاكتشاف السلبى إلى 40.8/100.000  في الاكتشاف النشط مما يعني أن الاكتشاف النشط يمكن أن يزيد معدل الرصد وهو من أهم أهداف و إستراتيجيات التحكم في مرض السل.